The Effect of Product Differentiation and Online Customer (Review on Purchase Decision Mediated By E-Trust Café Dikala 24 Hr Indrapasta Branch, Semarang City) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
Online Customer Review on Purchase Decisions Mediated by E-Trust at Café Dikala 24 Hr Indrapasta Branch, Semarang City. This research is a quantitative study. The population used in this study is the consumers of Café Dikala 24 Hr Indrapasta Branch, Semarang City, and the sample used is 160 consumers of Café Dikala 24 Hr Indrapasta Branch, Semarang City. This research employs a research method using simple random sampling technique with random sampling method. Data analysis in this study used Partial Least Square (PLS) program. The data analysis technique used was Structural Equation Modeling (SEM). The results of the analysis and discussion indicate the influence of product differentiation and online customer reviews on purchase decisions mediated by e-trust at Café Dikala 24 Hr Indrapasta Branch in Semarang City. This occurs because the research findings show that the P-Value of the influence of Product Differentiation on Purchase Decision mediated by E-Trust at Café Dikala 24 Hr Indrapasta Branch in Semarang City is0.036 < 0.05 and T-Statistic value of 2.304 > 1.96, which means the hypothesis of this research is accepted and the research shows that the P-Value of the effect of Online Customer Review on Purchase Decision Mediated by E-Trust at 24 Hr Indrapasta Cafe Branch in Semarang City is 0.021 < 0.05 and T-Statistic value of 2.097 > 1.96, which means the hypothesis of this research is accepted.
Keywords: Product Differentiation; Online Customer Reviews; Purchase Decisions; Trust